2021
DOI: 10.1007/s43032-021-00759-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential Distribution of Tryptophan-Metabolites in Fetal and Maternal Circulations During Normotensive and Preeclamptic Pregnancies

Abstract: Preeclampsia (PE) is a hypertensive pregnancy, which is a leading cause of maternal and fetal morbidity and mortality during pregnancy. L-Tryptophan (Trp) is an essential amino acid, which can be metabolized into various biologically active metabolites. However, the levels of many circulating Trp-metabolites in human normotensive pregnancies (NT) and PE are undetermined. This study quantified the levels of Trp-metabolites in maternal and umbilical vein sera from women with NT and PE. Paired maternal and umbili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…As described earlier, increased maternal tryptophan concentrations in preeclamptic compared to healthy term women are unlikely to reflect placental alterations. This might explain why the concentrations of tryptophan and kynurenine pathway metabolites did not differ between preeclamptic and healthy pregnancies at term in the maternal circulation, nor in the umbilical artery and umbilical vein [ 29 , 103 ]. However, kynurenine metabolite concentrations could still function as a biomarker, as kynurenic acid was increased in the circulation of women who later developed preeclampsia [ 104 ].…”
Section: Pathological Pregnanciesmentioning
confidence: 99%
“…As described earlier, increased maternal tryptophan concentrations in preeclamptic compared to healthy term women are unlikely to reflect placental alterations. This might explain why the concentrations of tryptophan and kynurenine pathway metabolites did not differ between preeclamptic and healthy pregnancies at term in the maternal circulation, nor in the umbilical artery and umbilical vein [ 29 , 103 ]. However, kynurenine metabolite concentrations could still function as a biomarker, as kynurenic acid was increased in the circulation of women who later developed preeclampsia [ 104 ].…”
Section: Pathological Pregnanciesmentioning
confidence: 99%
“…However, the rise in the concentrations of these metabolites was not large enough to result in statistically significant different concentrations between women with PE and uncomplicated pregnancies in this study. 45 Most studies did also not identify altered tryptophan concentrations in women with PE in the third trimester of pregnancy (Zhao et al 45 : QS = 4, median (SE) = 37.0 (1.2) in PE vs 34.5 (1.3) in controls, N = 40, P â©Ÿ .05 ; Liu et al 46 : QS = 4, N = 38, P â©Ÿ .05; JÀÀskelĂ€inen et al 43 : QS = 6, N = 71, P â©Ÿ .05). Only one study reported increased tryptophan in late-onset PE specifically (QS = 6, mean (SD): 42.8 (6.9) vs 32.7 (4.8) ”mol/L, N = 33, P < .001).…”
Section: Resultsmentioning
confidence: 99%
“…2 Instead, it might originate from another (yet unknown) source, and did not seem to affect the fetal kynurenic acid concentration. 45…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations